Associations of hair cortisol concentration with self-reported measures of stress and mental health-related factors in a pooled database of diverse community samples. (July 2014) - Wells, Samantha; Tremblay, Paul F.; Flynn, Andrea; Russell, Evan; Kennedy, James; Rehm, Jürgen; Van Uum, Stan; Koren, Gideon; Graham, Kathryn
Abstract A pooled database from diverse community samples was used to examine the associations of hair cortisol concentration (HCC) with self-reported stress and stress-linked mental health measures, including depression, anxiety, alcohol and drug use, disability and experiences with aggression. As part of innovative research using a mobile laboratory to study community mental health, data were pooled from five sub-studies: a random sample of the general population (n = 70), people who had received treatment for a mental health and/or substance use problem (n = 78), family members of people treated for mental health and/or substance use problems (n = 49), community volunteers who sometimes felt sad or blue or thought they drank too much (n = 83) and young adults in intimate partner relationships (n = 44). All participants completed a computerized questionnaire including standard measures of perceived stress, chronic stress, depression, anxiety, hazardous drinking, tobacco use, prescription drug use, illicit drug use, disability and intimate partner aggression. HCC was significantly associated with use of antidepressants, hazardous drinking, smoking and disability after adjusting for sub-study and potential confounders (sex, body-mass index, use of glucocorticoids and hair dyed). In addition, preliminary analyses suggest a significant curvilinear relationship between HCC and perceived stress; specifically, HCC increased with higher perceived stress but decreased at the highest level of stress. Overall, HCC was associated with mental health-related variables mainly reflecting substance use or experiencing a disability. The relationship between HCC and self-reported stress is unclear and needs further research.